LAND AND LABOR INSTITUTION IN URBAN AGRICULTURE IN SUPPORTING FOOD SECURITY IN MAKASSAR CITY - Diah Retno Dwi Hastuti; Abd. Rahim; Wardihan Sabar (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Limited land in urban areas shifts agricultural land to land belonging to institutions, which are increasingly narrow and uneven, resulting in the use of vacant land in several corners of urban areas. Meanwhile, some farmers use hired labor to harvest their crops. Both of these are considered to affect the food security of farmer households. This study used an explanatory method in which the collection of 165 farmer households was carried out using the snowball method. The data is then analyzed using a logit model. Based on the analysis results, household income, wife's education, land area, and land ownership institutions will increase household food security. Conversely, the number of family members and labor institutions will increase the chances of farmer households experiencing food insecurity. Therefore, policies are needed to protect agricultural land, especially those with ownership status.